Medication discrepancies despite pharmacist led medication reconciliation: the challenges of maintaining an accurate medication list in primary care - Stewart AL; Lynch KJ (Centro de Investigaciones y Publicaciones Farmaceuticas, 2014)
Objective: Describe the types of medication discrepancies that persist despite pharmacist-led medication reconciliation using the primary care electronic medical record (EMR). Methods: Observational case series study of established patients from an urban, indigent care clinic. Medication reconciliation was conducted immediately prior to the physician visit at baseline and return visit. Main outcome measures included: frequency, types, and reasons for discrepancies, patient knowledge, and adherence. Results: There was a 14.5% reduction in the number of patients with a discrepancy and the frequency of discrepancies was reduced by 7.3%. The rate of medication discrepancies in the chart was reduced by 31.3%. The most common type of discrepancy that persisted at follow up were medications listed on the chart that the patient stopped taking. Discrepancies were more likely to persist in Caucasian subjects when compared to African Americans. Conclusion: While pharmacist led medication reconciliation appears effective at reducing the likelihood of a medication discrepancy in the EMR, challenges persist in maintaining this accuracy specifically as it relates to patient driven changes to the medication regimen.